Different metabolic and genetic responses in citrus may explain relative susceptibility to Tetranychus urticae - Agut, Blas; Gamir, Jordi; Jaques, Josep A.; Hurtado-Ruiz, Mónica A.; Flors, Victor (2017)
Background: Life history parameters of the phytophagous spider mite Tetranychus urticae in citrus depend on the rootstock where the cultivar is grafted. To unveil the mechanisms responsible for this effect, the authors have carried out comparative experiments of T. urticae performance on two citrus rootstocks, the highly T. urticae-sensitive Cleopatra mandarin and the more tolerant sour orange. Results: Sour orange showed reduced leaf damage symptoms, supported lower mite populations and reduced oviposition rates compared with Cleopatra mandarin. Hormonal, metabolomic and gene expression analyses of the main defence pathways suggest a relevant role of the oxylipin and the flavonoid pathways in the response against T. urticae. Sour orange showed an increased activity of the JA pathway, which was hardly active in the most susceptible rootstock. Moreover, treatments with the LOX inhibitor Phenidone abolished the enhanced tolerance of sour orange. Therefore, oxylipin-dependent defence seems to be rootstock dependent. The metabolomic analysis showed the importance of the flavonoid pathway, which is implicated in the interaction between plants and their environment. Conclusion: The findings suggest that sour-orange enhanced tolerance to spider mites can be sustained by a combination of pre-existing and induced responses depending on high levels of flavonoids and a fast and effective activation of the oxylipin pathway.